2015
DOI: 10.1007/s11130-015-0473-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Conventional Microwave and Focused Microwave-assisted Extraction to Enhance the Efficiency of the Extraction of Antioxidant Flavonols from Jocote Pomace (Spondias purpurea L.)

Abstract: Jocote (Spondias purpurea L.) is rich in phenolic compounds which have antioxidant properties. The focused microwave-assisted extraction (FMAE) was compared with the conventional microwave-assisted extraction (MAE) to obtain flavonols from jocote pomace. The effects of parameters such as the extraction time, the temperature and the composition of the solvent mixture (i.e., the ethanol to water ration) were evaluated and optimized using a statistical experimental design approach. Response surface methodology (R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 33 publications
(32 reference statements)
0
6
2
1
Order By: Relevance
“…These results were different from those reported by Reis et al (2015), which extracted bioactive compounds from siriguela peels using microwave‐assisted conventional extraction. These authors found that the best result was obtained when a solution containing 80% ethanol in water was employed in the extraction process of phenolic compounds (flavonols).…”
Section: Resultscontrasting
confidence: 99%
See 2 more Smart Citations
“…These results were different from those reported by Reis et al (2015), which extracted bioactive compounds from siriguela peels using microwave‐assisted conventional extraction. These authors found that the best result was obtained when a solution containing 80% ethanol in water was employed in the extraction process of phenolic compounds (flavonols).…”
Section: Resultscontrasting
confidence: 99%
“…Our results showed that 30% ethanol was the best solvent solution to recover antioxidant compounds from siriguela peels, being different from the Reis et al (2015) data, which obtained better results using 80% ethanol at 68°C. In that study, the authors extracted antioxidant compounds (flavonols) from siriguela peels by focused microwave‐assisted extraction.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…This approach has been used to extract high-quality pectin with biomasses such as mango peels [ 155 ], citrus mandarin peels [ 156 ], fig skin [ 157 ], orange peel, apple pomace, mango peel, carrot pulp [ 158 ], pumpkin biomass [ 148 ], and banana peels [ 159 ]. The study conducted by Zin et al [ 160 ] showed that the highest microwave power used on the fruit waste (sour cherry pomace) was 700 W. Other biochemical compounds can also be obtained using this technique, such as antioxidants from black carrot pomace [ 161 ], pitaya peel [ 153 ], and mango seed kernels [ 162 ]; flavonoids from Jocote pomace [ 163 ]; anthocyanins from grape juice waste [ 164 ] and sour cherry pomace [ 165 ]; and essential oil from lemon peels waste [ 166 ]. Casas et al [ 167 ] also showed the potential of cocoa butter produced from mango kernel butter by extracting discarded seed kernels.…”
Section: Innovative Technologies Used For Bioactive Compound Extractionmentioning
confidence: 99%
“…For optimum yield extraction of the targeted compound, focused microwave-assisted extraction is preferred to conventional or household microwave ovens, as the parameters, namely the pressure and temperature, can be monitored [ 163 ]. A previous study showed that the combination of MAE with other methods could help produce high-yield compounds.…”
Section: Innovative Technologies Used For Bioactive Compound Extractionmentioning
confidence: 99%